2019
DOI: 10.1016/j.trecan.2019.02.008
|View full text |Cite
|
Sign up to set email alerts
|

The Gut–Brain Axis, Paving the Way to Brain Cancer

Abstract: The gut-brain axis formed by blood and lymphatic vessels paves the way for microbiota to impact the brain. Bacterial populations in the gut are a good candidate for a nongenetic factor contributing substantively to brain tumor development and to the success of therapy. Specifically, suppression of the immune system and induction of inflammation by microbiota sustain proliferative signaling, limit cell death, and induce angiogenesis as well as invasiveness. In addition, altered microbial metabolites and their l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 84 publications
1
51
0
Order By: Relevance
“…Recent studies demonstrate how certain microbial strains affect survival in melanoma and epithelial tumors treated with immunotherapy [ 19 , 20 ]. It is conceivable that similar findings may occur in CNS malignancies and potentially affect survival, via immunomodulatory responses through metabolites, neurotransmitters and cytokines [ 29 ]. However, further study of the relationship between CNS malignancies, metabolites, microbiome and response to treatment are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrate how certain microbial strains affect survival in melanoma and epithelial tumors treated with immunotherapy [ 19 , 20 ]. It is conceivable that similar findings may occur in CNS malignancies and potentially affect survival, via immunomodulatory responses through metabolites, neurotransmitters and cytokines [ 29 ]. However, further study of the relationship between CNS malignancies, metabolites, microbiome and response to treatment are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β strongly inhibits cytokine production, lymphocyte proliferation, and T cell differentiation. In contrast, IL-2 and IL-12 are released from Th 1 cells in normal tissues and are absent in glioblastoma tumors (Mehrian-Shai et al, 2019; Figure 1).…”
Section: Gut Dysbiosis and Microglial Dysfunctionmentioning
confidence: 99%
“…Interestingly, healthy individuals and cancer patients have different microbial flora in terms of population and diversity (Xuan et al, 2014). The influence of gut microbiota in various cancers has been extensively studied (Loo et al, 2017;Mehrian-Shai et al, 2019;Wong et al, 2019). However, its possible association with brain cancer is a new topic.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that the gut microbiota is also correlated with tumor development [58,59,60]. Recently, different reports have described the existence of a so called “gut-brain axis”, showing that the dysregulation of the gut microbiota may lead to the alterations of several processes predisposing to the development of a number of nervous system diseases, including cancer [61,62]. Moreover, individual genetic background may be linked to the prognosis of patients.…”
Section: Introduction: Glioblastoma Multiformementioning
confidence: 99%